Bioethical and legal issues of advance directives or living wills in the context of Spain - Atienza Macías, Elena; Armaza Armaza, Emilio José; de Miguel Beriain, Iñigo (Acta Bioethica, 2015)
The discrepancy generated by advanced directives is observed in several levels —ethical, legal and social—, and reaches even the terminological field, that is, the terms employed to refer to the issue are not distinct or indifferent at all: from living will to advanced directives to wishes previously expressed, etc., which confers some confusion about whether it refers to the same issue or to some legal insecurity, field otherwise very complex in this sense. In spite of the abundant legislation and doctrine about the issue, there is little information about the way to register the document, the possibility to consult it and the limits about its fulfillment. This article tries to offer more understanding of the issue considering the norms of Spain.